2016
DOI: 10.7470/jkst.2016.34.5.394
|View full text |Cite
|
Sign up to set email alerts
|

Impact Analysis of Weather Condition and Locational Characteristics on the Usage of Public Bike Sharing System

Abstract: This study aims to study the impact of weather conditions and locational characteristics of bike stations on the usage of public bike sharing system for efficient deployment and operation of public bike systems. Linear regression analysis is used to estimate the usage of public bikes of Goyang city. The statistical analysis shows that the usage rate increases with average temperature and decreases under high wind (over 7m/s) or high temperature (over 29°) condition. The usage rate of public bike sharing system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…They found that the bicycle usage rate was high in cities with mild winter weather but not much precipitation, and the usage rate decreased in very hot or humid cities. Similarly, Lee et al [15] analyzed the weather conditions affecting public bicycle usage in Goyang. They found that the public bicycle usage rate decreased when the precipitation, temperature, and wind speed were at least 10 mm, 29 • C, and 7 m/s, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that the bicycle usage rate was high in cities with mild winter weather but not much precipitation, and the usage rate decreased in very hot or humid cities. Similarly, Lee et al [15] analyzed the weather conditions affecting public bicycle usage in Goyang. They found that the public bicycle usage rate decreased when the precipitation, temperature, and wind speed were at least 10 mm, 29 • C, and 7 m/s, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the introduction of public bicycles is increasing in many local governments due to successful operation and increased bicycle use [4].…”
Section: Introductionmentioning
confidence: 99%